Morphometric studies of marigold (Tagetes erecta) var. Pusa Narangi Gainda: Impact of cold stress and mitigation strategies - TEJASWI, RAYAVARAPU; KUMAR, PRABHAT; SINGH, K P; SINGH, M C; PANWAR, SAPNA; PANWAR, SAPNA; JAIN, RITU; B K, TEJUKUMAR; A, POOJA; HIREMATH, VARUN (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during 2021 to 2023 at ICAR-Indian Agricultural Research Institute, New Delhi aimed to investigate the morphological changes of marigold (Tagetes erecta L.) var. Pusa Narangi Gainda under the influence of cold stress and mitigation techniques. The investigation included sowing the Pusa Narangi Gainda marigold variety on three distinct dates and subjecting the seedlings to two different growing environments [open field (E1) and protected conditions (E2)], each treated with various treatments and combinations included, T0, Control; T1, Salicylic acid (SA) @100 ppm; T2, SA @200 ppm; T3, SA @300 ppm; T4, Chitooligosaccharide (COS) @100 ppm; T5, COS @200 ppm; T6, COS @300 ppm; T7, Arbuscular mycorrhiza (AM) alone; T8, SA @100 ppm + AM; T9, SA @200 ppm + AM; T10, SA @300 ppm + AM; T11, COS @100 ppm + AM; T12, COS @200 ppm + AM and T13, COS @300 ppm + AM. The experiment was laid out in a factorial randomized block design (FRBD) with three replications. Parameters concerning plant growth, flowering, and yield were assessed and analysed. Findings indicated that plants cultivated within a low plastic tunnel, particularly those sown on October 15th exhibited superior growth and flowering characteristics compared to those grown in open field conditions. Upon examining different treatments, it was noted that combining COS at a concentration of 200 ppm with AM @10 g/plant yielded more favourable results compared to the control group and other treatments. This study underscores the advantageous effects of utilizing low plastic tunnels across different sowing dates and treatments on marigold plants' growth, flowering and yield attributes.